MANAJEMEN PESERTA DIDIK UNTUK MENINGKATKAN PRESTASI PESERTA DIDIK MTsN 2 TANGGAMUS - IDA EFIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Management of students can be interpreted as an effort to regulate students starting from these students entering school until they graduate from school. Knezevich (1961) defines student management or pupil personnel administration as a service that focuses on the management, supervision and services of students in the classroom and outside the classroom such as: introduction, registration, individual services such as developing overall abilities, interests, needs until he is mature. at school. MTsN 2 Tanggamus provides services to students, – namely the accentuation of services on the similarities and differences of children, this gives birth to the thought of the importance of student management at MTsN 2 Tanggamus to regulate how the demands of these two kinds of services can be met at school. Student management at MTsN 2 Tanggamus aims to regulate student activities so that these activities support the teaching and learning process at school; furthermore, the teaching and learning process in schools can run smoothly, orderly and regularly so that it can contribute to the achievement of school goals and overall educational goals. ABSTRAKManajemen peserta didik dapat diartikan sebagai usaha pengaturan terhadap peserta didik mulai dari peserta didik tersebut masuk sekolah sampai dengan mereka lulus sekolah. Knezevich (1961) mengartikan manajemen peserta didik atau pupil personnel administration sebagai suatu layanan yang memusatkan perhatian pada pengaturan, pengawasan dan layanan siswa di kelas dan di luar kelas seperti: pengenalan, pendaftaran, layanan individual seperti pengembangan keseluruhan kemampuan, minat, kebutuhan sampai ia matang di sekolah. MTsN 2 Tanggamus melakukan pelayanan terhadap siswa,– yakni aksentuasi pada layanan kesamaan dan perbedaan anak-anak, hal tersebut melahirkan pemikiran pentingnya manajemen peserta didik di MTsN 2 Tanggamus untuk mengatur bagaimana agar tuntutan dua macam layanan tersebut dapat dipenuhi di sekolah. Manajemen peserta didik di MTsN 2 Tanggamus bertujuan mengatur kegiatan-kegiatan peserta didik agar kegiatan-kegiatan tersebut menunjang proses belajar mengajar di sekolah; lebih lanjut, proses belajar mengajar di sekolah dapat berjalan lancar, tertib dan teratur sehingga dapat memberikan kontribusi bagi pencapaian tujuan sekolah dan tujuan pendidikan secara keseluruhan.